Pengaruh Digital Marketing, E-WOM, dan Citra Merek Terhadap Keputusan Pembelian Produk Nacific di Kota Batam - Vendi Vermanto; Realize, Realize (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the factors that influence consumer purchasing decisions for Nacific products in Batam City, with an emphasis on the role of digital marketing, E-WOM, and brand image. The research approach used is descriptive quantitative involving 204 respondents who have purchased Nacific products, selected through purposive sampling techniques based on Jacob Cohen's calculations to ensure the adequacy and representativeness of the sample. Data collection was carried out using a structured questionnaire, then analyzed through a series of statistical procedures including validity and reliability tests, classical assumption testing, multiple linear regression analysis, and hypothesis testing using t-tests and F-tests. The findings of the regression analysis revealed that the influence of digital marketing on purchasing decisions was recorded at 21.9%, E-WOM at 27.0%, and brand image at 34.0%. The coefficient of determination value of 0.722 confirms that digital marketing, E-WOM, and brand image simultaneously contribute 72.2% in explaining purchasing decisions. The results of the t-test and F-test indicate that digital marketing, e-WOM, and brand image each have a positive and significant influence on purchasing decisions, both partially and simultaneously.